Assessment of Body-worn Cameras Implementation Potential in Indonesia: A Systematic Literature Review - Putra, Mirza Triyuna; Yazid, Setiadi (Universitas Dharma Wacana, 2022)
Many studies have researched the application of BWCs or Body-Worn Cameras in various countries that have implemented the use of BWCs on law enforcement officers. Previous research has measured how effective the implementation of body cameras is in helping law enforcement accountability and transparency, what problems may arise, and how the public perceives the use of BWCs by law enforcement. This study conducts a methodological literature review on previous research sources that have discussed the implementation of BWCs in various countries with varied research methods, resulting in various conclusions. The main study of this study aims to determine the challenges and solutions for implementing BWCs by police officers and the public awareness of BWCs. The approach used is an updated guideline on PRISMA statement 2020 by compiling 13 main studies from 276 search results, starting from 2017 to 2022, that include problems and solutions for implementing BWCs and measuring people’s perceptions of BWCs usage. It was found in this study that some of the challenges in implementing BWCs by law enforcers are trust, racism, privacy concerns, cost, and IT capacity. Meanwhile, public perception is divided into two groups: those who support and do not support it. Several supporting factors to consider are that BWCs influence police behavior, accountability, legitimacy, transparency, and procedural justice.